Development of Nanoparticles of Alumina by Sol-Gel Method Using Inorganic Aluminum Salts as Precursors - Shaheen, Fadia; Qazia, Pervez Iqbal; Shah, Wajid Ali; Mirzab, Muhammad Latif (Biological Sciences - PJSIR, 2006)
Alumina nanoparticles were synthesized by homogeneous precipitation method from inorganic aluminum salt solutions using urea followed by calcination. The nanoparticles so produced were spherical and acicular with uniform particle size distribu- tion. The process describes synthesis of aluminum hydroxide Al(OH) and boehmite AlOOH, and their thermal decomposition into alumina (Al O ). The structural and morphological properties of the prepared aluminum hydroxide and nanocrystalline 2 3 powders were characterized by scanning eletron microscopy, differential thermal analysis and thermogravimetric analysis.